URGENSI PENDIDIKAN KARAKTER DI ERA PANDEMI COVID-19 - Hubbil Khair (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Character education is a values live transformation wich developed for childs personality. The purpose of this study is for giving description of urgency character education on pandemic Covid-19. Exemplary is one of important aspect to reach character education on pandemic Covid-19 because character education is one of personality that must applied in life activities. All component at home, school, environment and public they must help each other to reach attitude and behavior according of Indonesian personality on pandemic Covid-19. The values of character is expected can be motivatios for doing health protocol with awareness and pleasure.